Recovery process of Li, Al and Si from lepidolite by leaching with HF - Rosales, Gustavo Daniel (2017)
This work describes the development of a new process for the recovery of Li, Al and Si along with the proposal of a flow sheet for the precipitation of those metals. The developed process is comprised of lepidolite acid digestion with hydrofluoric acid, and the subsequent precipitation of the metals present in the leach liquor. The leaching operational parameters studied were: reaction time, temperature and HF concentration. The experimental results indicate that the optimal conditions to achieve a Li extraction higher than 90% were: solid-liquid ratio, 1.82% (w/v); temperature, 123 °C; HF concentration, 7% (v/v); stirring speed, 330 rpm; and reaction time, 120 min. Al and Si can be recovered as Na3AlF6 and K2SiF6. LiF was separated from the leach liquor during water evaporation, with recovery values of 92%.